17z-15z-1=9

Simple and best practice solution for 17z-15z-1=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17z-15z-1=9 equation:


Simplifying
17z + -15z + -1 = 9

Reorder the terms:
-1 + 17z + -15z = 9

Combine like terms: 17z + -15z = 2z
-1 + 2z = 9

Solving
-1 + 2z = 9

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 2z = 9 + 1

Combine like terms: -1 + 1 = 0
0 + 2z = 9 + 1
2z = 9 + 1

Combine like terms: 9 + 1 = 10
2z = 10

Divide each side by '2'.
z = 5

Simplifying
z = 5

See similar equations:

| 32=5n+2 | | 5y-2+y+19=7y+20-4y | | (1900)(0.059)= | | 7y-3y+5y+1= | | 2.1+3.4=-7.2 | | -7+3w=-16 | | -4(c+10)=-8 | | 66.6=6(m+3.4) | | R(t)=46.8-0.075t | | 9r+5=24r+8 | | 6k^2-3k+1=0 | | 13=d-6 | | (11x-7)+(5x-3)=188 | | 35m+5n+15=0 | | 6m-7-3m=9m+5 | | 9y-7y+2=18 | | 3z+5=3z+17 | | 10x-15=-4 | | 8-5x+2-12+12x=6x-15x+8+15x | | 5(4x+2)=a+b | | F(x-3)-f(x)=5x^2-2x+1 | | 4w-8+12w+2=-2w-10 | | 5x-13=63 | | .25x=.08x+25 | | 4(p+5)=6p+20 | | 3(n+6)=4(n+6)-(n+6) | | 4p-9=8 | | 9+3u=-9+6u | | (x-2)(x-i)(x+i)=0 | | 9.60b-35.20=200 | | 4(7+3)+.5= | | 5b^2+7b-2= |

Equations solver categories